2017
DOI: 10.21272/jnep.9(3).03043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing in Physical Properties of NiO Nanostructure Thin Film

Abstract: Nickel oxide was deposited on highly cleaned glass substrates using spray pneumatic technique. The effect of precursor molarity on structural, optical and electrical properties has been studied. The XRD lines of the deposited NiO were enhanced with increasing precursor molarity due to the improvement of the films crystallinity. It was shown that the average of the crystalline size of the deposited thin films was calculated using Debye-Scherer formula and found 46.62 for as-deposited sample and 119.89 nm for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
1
0
0
Order By: Relevance
“…The values of band gap Eg is 3.61 eV for undoped sample, whereas the values of E g gradually decreases from 3.60 to 3.48 eV for Co-doped samples from 3 to 12 at.%. This is in good agreement with previous research reports by different groups [27,28], where they found that the bandgap of NiO films varies between 3.4 eV and 4.0 eV. The band gap is found to decrease with an increase in the Co doping concentration; this suggests a change in the NiO electronic structure i.e the suggests a change in the crystallite growth, defects or vacancies in the NiO crystal which can create new energy levels.…”
Section: Optical Propertiessupporting
confidence: 92%
“…The values of band gap Eg is 3.61 eV for undoped sample, whereas the values of E g gradually decreases from 3.60 to 3.48 eV for Co-doped samples from 3 to 12 at.%. This is in good agreement with previous research reports by different groups [27,28], where they found that the bandgap of NiO films varies between 3.4 eV and 4.0 eV. The band gap is found to decrease with an increase in the Co doping concentration; this suggests a change in the NiO electronic structure i.e the suggests a change in the crystallite growth, defects or vacancies in the NiO crystal which can create new energy levels.…”
Section: Optical Propertiessupporting
confidence: 92%
“…Le mélange est agité à 60°C pendant 2heures pour obtenir une eau limpide et une solution homogène puis le mélange a été refroidi à optique des films minces obtenus est de 3,64 eV et de 2,98 eV respectivement des échantillons non recuits et ceux recuits. La conductivité de l'échantillon non recuit est de l'ordre de 0,04125 𝛺 −1 cm -1 et celle de l'échantillon recuit est de 0,09241 𝛺 −1 cm -1[74]. Universitat Politècnica de València / Instituto Diseño y Fabricación (IDF)…”
unclassified